KONTEKSTUALISASI HADIST TENTANG THA’UN DALAM MENANGANI PANDEMI COVID-19 - Fathul Wahab, M. Royyan Nafis; Najib, Ahmad Ainun; Hikmah, Sofi Faiqotul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study departs from the problem of handling the Covid-19 (coronavirus disease) pandemic in Indonesia. In its history, during the time of the Prophet Muhammad SAW. There was a pandemic tha’un and found various ways of handling the Prophet Muhammad in dealing with tha’un in the hadith literature. The subject of this research is the Hadith of the Prophet written in the book of hadith and the object of this research is the hadith which explains about tha’un. The purpose of this study is to find the contextualization of the hadith about tha’un as a reference for dealing with Covid-19 in Indonesia. This research is a qualitative research with a type of library research. The findings of this study are the result of contextualization of the hadith about tha’un with the state of the Covid-19 outbreak in Indonesia which states that the handling of Covid-19 must be done by doing a combination of strict restrictions on the rules of entry and exit of areas affected by Covid-19 and conducting physical distancing by taking into account the stabilization of important sectors in Indonesia.